2005
DOI: 10.1017/s0031182005008395
|View full text |Cite
|
Sign up to set email alerts
|

Nematode biology and larval development of Thelazia callipaeda (Spirurida, Thelaziidae) in the drosophilid intermediate host in Europe and China

Abstract: Thelazia callipaeda, commonly known as the 'oriental eyeworm', has been recently reported in Italy and other European countries. The insect/s that act as intermediate hosts and details of larval development inside the vector remain unclear. In order to (1) demonstrate the species of fly that may act as vector/s for T. callipaeda in southern Italy (Site A) and China (Site B) and (2) describe the larval development of the nematode in the body of flies, 847 Phortica (Drosophilidae) flies were collected from the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 15 publications
7
102
1
2
Order By: Relevance
“…Adult whitish nematodes of about 0.5-2 cm and the first larval stages (L1) can be found particularly under the third eye lid provoking lacrimation, conjunctivitis or even keratitis and corneal ulcer (Otranto and Traversa 2005). In Europe, T. callipaeda is transmitted by Phortica variegata, as shown in Italy under natural and experimental conditions (Otranto et al 2005a). …”
Section: Introductionmentioning
confidence: 98%
“…Adult whitish nematodes of about 0.5-2 cm and the first larval stages (L1) can be found particularly under the third eye lid provoking lacrimation, conjunctivitis or even keratitis and corneal ulcer (Otranto and Traversa 2005). In Europe, T. callipaeda is transmitted by Phortica variegata, as shown in Italy under natural and experimental conditions (Otranto et al 2005a). …”
Section: Introductionmentioning
confidence: 98%
“…Recent investigations identified Phortica variegata (Diptera, Drosophilidae) as a potential vector and intermediate host of T. callipaeda under experimental and natural conditions (Otranto et al, 2005a;2006b). An ecological niche model suggested that the climate of large areas of Europe could be suitable habitats for this vector (Otranto et al, 2006a) and thus are potentially endemic for T.…”
Section: Introductionmentioning
confidence: 99%
“…However, P. variegata, the already proven intermediate host and vector for the eyeworm in Europe [18,19], had never been described in Serbia. Knowing this vector is the prerequisite for autochthonous thelaziosis in any area, as well as the fact that Serbia is part of areas in Europe expected as suitable for P. variegata [27], further investigations concerning this issue are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Human ocular infections caused by T. callipaeda detected in endemic areas of Italy, France and Spain implicated the epidemiological importance of this parasite and the need for control measures [16,17]. The intermediate host and vector for T. callipaeda in Europe is the fruit fl y Phortica variegata (Drosophilidae, Steganinae), which is confi rmed under both experimental and natural conditions [18,19].…”
Section: Introductionmentioning
confidence: 98%